Legible lesbian lines: The bilingual poetry of Irena Klepfisz. Issue 1 (2nd January 2019) - Weiman-Kelman, Zohar
Abstract: This article focuses on the poetry of Jewish lesbian poet Irena Klepfisz, written in New York starting in the 1970s. While drawing on the tradition of Yiddish women's poetry from the first half of the twentieth century, both as scholar and poet, Klepfisz also creates a brand new, bilingual, Yiddish-English poetic mode. By mobilizing both Yiddish and English to voice her poetic and political concerns, Klepfisz stages the English/Yiddish encounter as a site where dominant norms in both languages can be challenged and new possibilities emerge. Exploring both her turn to the past and her bilingual poetry, this article reveals how Klepfisz puts her politics and scholarship to poetic practice and suggests that Klepfisz offers a model of queer translation that undoes the borders between past and present, English and Yiddish, creating a unique mode of Jewish lesbian reclamation and invention.